Analisa Gardu Traksi Boilevard Selatan Akibat Jatuh Tegangan - Triwijaya, Santi; Nugroho, Agung; Pradipta, Andri; Wati, Trisna (Institut Teknologi Adhi Tama Surabaya, 2025)
South Boulevard traction substation with the output of the rectifier of 750VDC and 4000A against LRV loading under normal and abnormal conditions. This research was conducted with data sources in the form of specifications for traction substation equipment, 3rd rail specifications, and LRV specifications. The power generated by the South Boulevard traction substation under normal and upnormal conditions will be compared with the LRV load when the headway is narrowed, the train set is added, and the voltage drop is measured. The traction substation is said to be able to bear the load when the power used by the load does not exceed the power provided by the traction substation so that the LRV operation can run. The results of the analysis stated that under normal conditions the capacity of the South Boulevard to Pulomas traction substation obtained the smallest value of 2 minutes headway for 2 train sets at 1806,1KW power with a drop voltage of 30V and the capacity of the South Boulevard to North Boulevard traction substation obtained the smallest value of 2 minutes headway for 2 train sets at 1697,9KW power with a drop voltage of 27,4V. Upnormal condition of the capacity of the South Boulevard to Pegangsaan Dua traction substation, the smallest headway value was 5 minutes for 2 train sets at 1643,2KW power with a drop voltage of 45V and the capacity of the South Boulevard to Equestrian traction substation was obtained the smallest value of 4 minutes headway for 2 train sets at 1651,5KW power a drop voltage of 36,4V.